AKTIVITAS INHIBISI ENZIM ALFA-GLUKOSIDASE DARI EKSTRAK BUNGA KERSEN (Muntingia calabura L.) SECARA IN VITRO - Azzahra, Resqinah; Maryam, St.; Tahir, Masdiana (Makassar Pharmaceutical Science Journal (MPSJ), 2023)
The cherry tree is one of the plants that has great potential to be utilized because it contains several beneficial bioactive compounds, one of which is flavonoids.. The purpose of this research is to determine the alpha-glucosidase enzyme inhibition activity of an ethanol extract of cherry blossoms (Muntingia calabura L.) in vitro using a microplate reader instrument. The research method begins with preparing the sample by maceration using 96% ethanol as a solvent, followed by testing the inhibition of alpha-glucosidase enzyme activity using p-nitrophenyl- α-D-glucopyranoside (PNPG) substrate and acarbose as a comparison. The potential of a compound to inhibit enzyme activity can be determined by calculating the IC50. The results showed that the ethanol extract of cherry blossoms (Muntingia calabura L.) has an IC50 value of 135.53 µg/mL, higher than the IC50 value of acarbose at 41.17 µg/mL.